Online Club Reporting (OCR) System / Nur Syahirah Zahari - Zahari, Nur Syahirah (2017)
HEP department of UiTM cawangan Terengganu Campus Dungun currently operated manually in submission activity report. The problem with the submission is student need to submit activity report in limit time which is office hour only. In addition, data loss because staff cannot trace the details of the activity report for every club. Online Club Reporting (OCR) System for HEP department is developed to help student to ease the submission activity report. Reports can be generated easily using this system. The Rapid Application model methodology is used in the development of the system. This system has been evaluated by three expert users for the feedback and the recommendation. Besides that, this system has been evaluate with three experts and 30 respondents for user evaluation. Based on the user evaluation, the highest mean for interface construct is 4.03 with 0.61 the standard deviation. The perceives ease of use construct show the highest mean is 3.93 with standard deviation is 0.58. Then, the highest mean is 3.97 with standard deviation 0.67 shows for the usability and satisfaction construct. The consistency construct shows the highest mean is 4.07 with 0.52 of standard deviation. The last construct is efficiency construct shows that 4.10 is the highest mean with 0.71 is the standard deviation. In a nutshell, the recommendation for future enhancement will improve the completeness of submission activity reports using the format provided.